How to increase the prestige of a scientist in the Russian Federation - O. M. Makhalina; V. N. Mahalin (Вестник университета)
The Russian science, according to the existing scientific resources, occupies leading places on many positions, demonstrates serious achievements in many fields, but low overall effectiveness. In the development of science, systemic problems are manifested due to numerous factors, the most important of which are considered in the work. The analysis of the modern development of science has revealed its main challenges. Special attention is paid to the problems of staffing the scientific and technical complex and identifying the causes of the decline in the scientist’s prestige. In Russia, the number of personnel employed in science has been constantly decreasing for many years. The number of postgraduates and doctoral students as well as the amount of dissertation defenses, has decreased 4–7 times over the past four years, and the age structure of the scientific staff has been deformed. The popularity of the scientist has decreased several times. Based on the analysis, the main factors of declining popularity are identified in the work: profession of the scientist is not prestigious; there is a low salary level; there are no mechanisms for popularising the profession; there is no qualitative assessment of the scientist’s work. Proposals for staffing scientific activities and increasing the prestige of the scientist’s work are formulated: increase of the cost of science; elimination of the problem of the scientific personnel’s aging; significant increase in the material support of the scientific personnel; expansion of the possibilities of using grant financing for basic research. Special attention is paid to solving the tasks of improving scientific activity, which are formulated in national projects.